Gut Microbiome Dysbiosis in Alcoholism: Consequences for Health and Recovery - Day, Andrew Whittier; Kumamoto, Carol A. (Frontiers in Cellular and Infection Microbiology, 2022)
Since the mid 1980’s, the impact of gastrointestinal (GI) microbiome changes during alcohol use disorder has been an area of significant interest. This work has resulted in the identification of specific changes in the abundance of certain members of the GI microbiome and the role these changes play in a variety of alcohol related disorders (i.e. alcoholic liver disease). Interestingly, some findings suggest a possible role for the GI microbiome in alcohol addiction or withdrawal. Unfortunately, there is a significant gap in knowledge in this area. Here we describe differences in the GI microbiome of alcoholic and non-alcoholic individuals and discuss the possible impact of microbes on the gut-brain axis, which could impact alcohol related behaviors (i.e. addiction). Understanding the role of the GI microbiome in alcohol related disorders will potentially lead to the development of successful microbiome-targeted therapeutics to help mitigate these disorders.